Faktor-Faktor yang Memengaruhi Luas Pengungkapan Laporan Tahunan pada Sub Sektor Makanan dan Minuman di BEI Tahun 2019-2022 - Maulidianita, Hervira; Pahala, Indra; Yusuf, Muhammad (LPPM Universitas Negeri Jakarta, 2023)
This research was conducted to analyze leverage, profitability, company age and public share ownership on the extent of annual report disclosure. The research object used is the food and beverage subsector on the IDX in 2019-2022. This data was processed in a panel manner using Eviews version 13. The sample found was 23 companies using the purposive sampling method. Based on this research, it was found from the results of hypothesis testing that the company age variable had a significant positive influence on the extent of annual report disclosure. Meanwhile, the variables leverage, profitability and public share ownership have no influence on the extent of annual report disclosure. It is concluded that leverage, profitability and public share ownership are financial reports that must be disclosed according to SEOJK No.30/SEOJK.04/2016. Therefore, food and beverage companies are expected to continue to develop their business so that the company can survive for a long time and have a long life in the business world, so that the company can present a broader annual report which not only discloses information that must be disclosed but also provides additional voluntary information. This is done to attract the attention of users of food and beverage companies' annual reports.